Performance of the 2015 American College of Rheumatology/European League Against Rheumatism gout classification criteria in Thai patients - Worawit Louthrenoo (2018)
© 2017, Springer-Verlag Berlin Heidelberg. To evaluate the sensitivity and specificity of the 2015 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) gout classification criteria in Thai patients presenting with acute arthritis in a real-life setting. Data were analyzed on consecutive patients presenting with arthritis of less than 2 weeks duration. Sensitivity and specificity were calculated by using the presence of monosodium urate (MSU) crystals in the synovial fluid or tissue aspirate as gold standard for gout diagnosis. Subgroup analysis was performed in patients with early disease (≤2 years), established disease ( > 2 years), and those without tophus. Additional analysis also was performed in non-tophaceous gout patients, and patients with acute calcium pyrophosphate dihydrate crystal arthritis were used as controls. One hundred and nine gout and 74 non-gout patients participated in this study. Full ACR/EULAR classification criteria had sensitivity and specificity of 90.2 and 90.0%, respectively; and 90.2 and 85.0%, respectively, when synovial fluid microscopy was excluded. Clinical-only criteria yielded sensitivity and specificity of 79.8 and 87.8%, respectively. The criteria performed well among patients with early and non-tophaceous disease, but had lower specificity in patients with established disease. The variation of serum uric acid level was a major limitation of the classification criteria. The ACR/EULAR classification criteria had high sensitivity and specificity in Thai patients presenting with acute arthritis, even when clinical criteria alone were used.